A randomized controlled trial to optimize patient's selection for endovascular treatment in acute ischemic stroke (SELECT2): Study protocol. Issue 6 (July 2022) - Sarraj, Amrou; Hassan, Ameer E; Abraham, Michael; Ribo, Marc; Blackburn, Spiros; Chen, Michael; Hussain, Muhammad Shazam; Pereira, Vitor Mendes; Ortega-Gutierrez, Santiago; Sitton, Clark; Lavori, Phillip W; Cai, Chunyan; et al.
Rationale: Randomized evidence for endovascular thrombectomy safety and efficacy in patients with large core strokes is lacking. Aims: To demonstrate endovascular thrombectomy efficacy and safety in patients with large core on non-contrast CT or perfusion imaging (CT/MR) and determine if there is heterogeneity of treatment effect in large cores based on the imaging modality. Design: SELECT2 is a prospective, randomized, multi-center, assessor-blinded controlled trial with adaptive enrichment design, enrolling up to 560 patients. Procedure: Patients who meet the clinical criteria and have anterior circulation large vessel occlusions with large core on either NCCT (ASPECTS 3–5) or perfusion imaging (CTP [rCBF < 30%] and/or MRI [ADC < 620] ≥ 50 cc) will be randomized in a 1:1 ratio to undergo endovascular thrombectomy or medical management (MM) only up to 24 h of last known well. Study outcomes: The distribution of 90-day mRS scores is the primary outcome. Functional independence (mRS = 0–2) rate is a secondary outcome. Other secondary outcomes include safety (symptomatic ICH, neurological worsening, mortality) and imaging outcomes. Analysis: A normal approximation of the Wilcoxon-Mann-Whitney test (the generalized likelihood ratio test) to assess the primary outcome. Functional independence rates, safety and imaging outcomes will also be compared. Discussion: The SELECT2 trial will evaluate endovascular thrombectomy safety and efficacy in large cores on either CT or perfusion imaging and may provide randomized evidence to extend endovascular thrombectomy eligibility to larger population. Registration: ClinicalTrials.gov–NCT03876457